Crude Oil Biodegradation by a Biosurfactant-Producing Bacterial Consortium in High-Salinity Soil - Weiwei Chen; Jiawei Sun; Renping Ji; Jun Min; Luyao Wang; Jiawen Zhang; Hongjin Qiao; Shiwei Cheng (Journal of Marine Science and Engineering, 2024)
Bioremediation is a promising strategy to remove crude oil contaminants. However, limited studies explored the potential of bacterial consortia on crude oil biodegradation in high salinity soil. In this study, four halotolerant strains (Pseudoxanthomonas sp. S1-2, Bacillus sp. S2-A, Dietzia sp. CN-3, and Acinetobacter sp. HC8-3S), with strong environmental tolerance (temperature, pH, and salinity), distinctive crude oil degradation, and beneficial biosurfactant production, were combined to construct a bacterial consortium. The inoculation of the consortium successfully degraded 97.1% of total petroleum hydrocarbons in 10 days, with notable removal of alkanes, cycloalkanes, branched alkanes, and aromatic hydrocarbons. Functional optimization showed that this consortium degraded crude oil effectively in a broad range of temperature (20–37 °C), pH (6–9), and salinity (0–100 g/L). In salt-enriched crude-oil-contaminated soil microcosms, the simultaneous treatment of bioaugmentation and biostimulation achieved the highest crude oil degradation rate of 568.6 mg/kg/d, compared to treatments involving abiotic factors, natural attenuation, biostimulation, and bioaugmentation after 60 days. Real-time PCR targeting the 16S rRNA and alkB genes showed the good adaptability and stability of this consortium. The degradation property of the constructed bacterial consortium and the engineered consortium strategy may have potential use in the bioremediation of crude oil pollution in high-salinity soil.